(untitled) (AYUSHDHARA, 2021)
Objectives: This study was conducted to evaluate the effectiveness of Palashapushpa churna in the Management of Vatarakta (Gouty Arthritis). Materials and Methods: A single blind clinical trial was conducted at Department of Dravyaguna, Dr.B.R.K.R Govt. Ayurvedic Hospital, Erragadda, Hyderabad. 30 patients were selected and trial drug was advocated in a dose of 3 gm Palashapushpa churna twice a day with water as Anupana. Treatment was given for 45 days with the result assessment recorded at every 15 days. Subjective and objective parameters were analyzed before and after the treatment. In subjective parameters Shula, Daha, Shotha, Raga, Sthabdata are taken, while Serum uric acid levels is considered as objective parameter. Results: Out of 30 patients, Sula, Daha, Shotha, Sthabdata was found in all patients, Raga was found in 6 patients, which suggests the severity of condition. After treatment it was observed that Sula is found to be relieved by 93.33% of patients, Daha and Shotha is found to be relieved by 60%, Raga is found to be relieved by20% of patients, Sandhi stabdata is found to be relieved by 80% of patients . It is observed that Sandhi shula and Sandhi sthabdata was got good relief, Sandhi daha and Sandhi shotha was got moderate relief. Sandhi raga was got mild relief. The average serum uric acid levels in the patients of Vatarakta before the treatment is 2.13 after the treatment with administration of Palashapushpa churna orally it was brought down to the average of 1.13. The average decrease in the levels of uric acid with highly significant (P<0.001). Conclusion: Palasha pushpa churna prepared as per the textual standards is highly effective in Vatarakta and showing a way out to the individual suffering from this chronic disease. The study confirmed the effect of trial drug in Vatarakta (Gouty arthritis) in improving the quality of life of patients without any untoward effects.